Portfolio management in practice - Brentani, Christine (Essential Capital Markets S.)
As individuals are becoming more and more responsible for ensuring their own financial future, portfolio or fund management has taken on an increasingly important role in banks' ranges of offerings to their clients. In addition, as interest rates have come down and the stock market has gone up and come down again, clients have a choice of leaving their saving in deposit accounts, or putting those savings in unit trusts or investment portfolios which invest in equities and/or bonds. Individuals are becoming aware that they might need to top up government pension allocations. Likewise, corporations who run employee pension schemes have to ensure that they are able to cover their current and future liabilities. Investing in unit trusts or mutual funds is one way for individuals and corporations alike to potentially enhance the returns on their savings. Introduction to Portfolio Management covers the: *Theoretical underpinnings of portfolio management *Basics of portfolio construction *Constraints to be considered when building a client portfolio *Types of analysis used for asset allocation and stock selection *Main types of funds available to investors *Inspired from the basic entry level training courses that have been developed by major international banks worldwide. *Will enable MSc Finance students, MBA students and those already in the finance profession to gain an understanding of the basic information and principles underlying the topic under discussion *Questions with answers, study topics, practical "real world" examples and text with an extensive bibliography and references ensure learning outcomes can be immediately applied.